Salvaged Failed Roof Rings and Antiprotrusion Cages: Surgical Options and Implant Survival. Issue 2 (March 2013) - Tangsataporn, Suksan; Abolghasemian, Mansour; Kuzyk, Paul R.; Backstein, David J.; Safir, Oleg A.; Gross, Allan E.
Introduction: Failed acetabular reinforcement rings (ARR) (roof rings and antiprotrusion cages) may require another ARR reconstruction or another type of acetabular device with or without a bone graft. The purpose of this study was to propose surgical options for salvage of failed ARRs and to compare the failure rate of each surgical option. Materials and methods: We reviewed 33 first ARRs (12 roof rings and 21 antiprotrusion cages) which were revised and converted to a new acetabular reconstruction. Operative reports, radiographs, and clinical data were evaluated. Minimum follow-up was 24 months (average 57 months; range 24-209 months). Results: 33 failed first ARRs were converted to one of three types of acetabular reconstruction, Trabecular Metal (TM) cup in 14, cup-cage in 7 and a second ARR in 12. The TM cup group (TM cup and cup-cage) had a significantly longer survival than the second ARR group (P = 0.025) on log-rank analysis. Discussion: Treatment of a failed first ARR by a TM cup and a cup-cage provides better results when compared to treatment by a second ARR. Restoration of bone stock is the main factor in determining whether a TM cup or cup-cage rather than another conventional ARR can be used.